LIFE EXPECTANCY, DIRECT FOREIGN INVESTMENTS, TRADE OPENNESS AND ECONOMIC GROWTH IN E7 COUNTRIES: HETEROGENEOUS PANEL ANALYSIS (Third Sector Social Economic Review, 2019)
The purpose of this study is to apply an empirical analysis of the correlation among life expectancy, net direct foreign investment inflows, trade openness and economic growth in E7 countries between 1992 and 2016. To this end, these variables are tested in terms of their cointegration and causality relations. The empirical evidence indicates a long term dependence of variables among each other. The causality tests conclude that a reciprocal causality exists between economic growth and life expectancy, between economic growth and trade openness and between life expectancy and trade openness. According to the tests’ findings, there is a one-way causality from economic growth to foreign direct investment, from life expectancy to foreign direct investment and from openness to foreign direct investment. The study includes policy recommendations at the conclusion section.
Keywords: Life Expectancy; Trade Openness; Direct Foreign Investments; Economic Growth; E7 Countries.